Multi-walled CNT-induced phase behaviour of poly(vinylidene fluoride) and its electro-mechanical properties - Rath, Sangram K.; Dubey, Sachin; Kumar, G. Sudheer; Kumar, Sanjay; Patra, A. K.; Bahadur, Jitendra; Singh, A. K.; Harikrishnan, G.; Patro, T. Umasankar (Journal of Materials Science, 2014)
A simple two-step process was used to disperse acid functionalizedmulti-walled carbon nanotubes (CNTs) in poly(vinylidene fluoride) (PVDF). While the neat solvent-cast PVDF showed coexistence of alpha- and beta-phases; the composite films exhibited only beta-phase crystals. Further studies on the crystalline behaviour, using differential scanning calorimetry and small-angle X-ray scattering techniques showed an increase in the percentage of crystalline phase with CNT. The network formed by CNTs in the matrix reduced the macroscopic electrical resistivity of composite films. The dielectric constant increased with CNT loading. Further, these composites were investigated for its electromagnetic wave absorbance (EWA) and strain sensing properties. The EWA properties were studied in the X-band (6-12 GHz) region. A maximum of similar to 37 dB reflectivity loss at similar to 9.0 GHz was obtained in a similar to 25 mu m thick PVDF film containing only 0.25 wt% of functionalized CNT. Preliminary studies showed a systematic change in electrical resistance by the application of dynamic bending strain in nanocomposite film. The film also showed a significant improvement in mechanical stiffness owing to efficient stress transfer from matrix to filler, the property desirable for a good strain sensor. In view of the unique combination of EWA and electro-mechanical properties, the nanocomposite films are expected to serve as a multifunctional material for strain sensing in health monitoring as well as in radar absorption.

Repurposing Ivacaftor for treatment of staphylococcus aureus infections - Thakare, R.; Das, S.; Vasudevan, N.; Jachak, G.R.; Reddy, D.S.; Dasgupta, A.; Chopra, S. (International Journal of Antimicrobial Agents, 2017)
Drug repurposing of non-antimicrobials is a novel method to augment a seriously depleted drug pipeline for targeting drug–resistant pathogens. This article highlights the potent antimicrobial activity of Ivacaftor against Staphylococcus aureus, including vancomycin– and other multidrug–resistant strains. The potent activity of Ivacaftor in vivo is also demonstrated in a murine neutropenic thigh infection model. Taken together, these results support the potential of Ivacaftor as an antimicrobial agent for the treatment of staphylococcal infections. © 2017 Elsevier B.V. and International Society of Chemotherapy